2023
DOI: 10.1038/s43856-023-00245-5
|View full text |Cite
|
Sign up to set email alerts
|

B cell response after SARS-CoV-2 mRNA vaccination in people living with HIV

Abstract: Background Limited longitudinal data are available on immune response to mRNA SARS-CoV-2 vaccination in people living with HIV (PLWHIV); therefore, new evidence on induction and persistence of spike-specific antibodies and B cells is needed. Methods In this pilot study we investigated the spike-specific humoral and B cell responses up to six months after vaccination with two doses of mRNA vaccines in 84 PLWHIV under antiretroviral therapy compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Such HIV-associated alterations of B-cell maturation may explain findings by Hwa et al showing that the antibody response in the second wave of SARS-CoV-2 infections was affected by HIV status, with PWH mounting less effective IgG responses to the Beta variant [ 72 ]. Of note, comparable alterations in the phenotype of SARS-CoV-2-specific B cells in PWH compared to heathy controls have also been observed after SARS-CoV-2 mRNA vaccination [ 84 ]…”
Section: Immune Response To Sars-cov-2 Infection In Pwhmentioning
confidence: 98%
“…Such HIV-associated alterations of B-cell maturation may explain findings by Hwa et al showing that the antibody response in the second wave of SARS-CoV-2 infections was affected by HIV status, with PWH mounting less effective IgG responses to the Beta variant [ 72 ]. Of note, comparable alterations in the phenotype of SARS-CoV-2-specific B cells in PWH compared to heathy controls have also been observed after SARS-CoV-2 mRNA vaccination [ 84 ]…”
Section: Immune Response To Sars-cov-2 Infection In Pwhmentioning
confidence: 98%
“…Another 13 studies were further removed for failing to report seroconversion (n = 6), cross-sectional studies (n = 5), reviews (n = 2) (File S1). Finally, 50 studies with a total of 7160 patients living with HIV were included in our meta-analysis 11 , 12 , 17 64 , 30 studies were included for qualitative analysis of serological antibody titers (Supplementary Tables S3 – S5 ); 46 studies 11 , 12 , 17 25 , 27 32 , 34 39 , 41 56 , 58 64 were included for quantitative analysis of pooled seroconversion rate; 34 studies 11 , 12 , 17 20 , 23 25 , 27 , 31 , 35 , 36 , 38 , 39 , 41 46 , 48 51 , 53 , 55 , 56 , 59 64 were used for quantitative analysis of pooled risk ratios for seroconversion following the uncomplete, complete, or booster dose of COVID-19 vaccines between patients living with HIV and HIV-negative vaccine counterparts (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of course, this may be attributed to the fact that the included studies were mRNA vaccine-related. Polvere et al ( 79 ) demonstrated that the second vaccination of mRNA vaccine elicits B-cell responses that are quantitatively similar between PLWH and HC, but there are important differences in terms of antibody functionality and phenotypes of memory B cells. More evidence is needed to support changes in B-cell antibody function in PLWH after booster vaccination with COVID-19.…”
Section: Discussionmentioning
confidence: 99%